Development of balance in young kayakers in the initial stage of training - Farkhodovich, I. B. (European Journal of Balance and Reflection in Educational Sciences, 2020)
The huge competition on international scene in rowing demands indefatigable and constant search of new, effective agents, receptions, approaches and methods of work with beginning young oarsmen. Thus, it is necessary to notice, that to a scientific substantiation of training process as at adults «masters of an oar» rowing, and at juvenile sportsmen, the insufficient attention is paid.